Liquid Sensing: Spoof Plasmon Surfaces: A Novel Platform for THz Sensing (Advanced Optical Materials 8/2013). Issue 8 (21st August 2013) - Ng, Binghao; Wu, Jianfeng; Hanham, Stephen M.; Fernández‐Domínguez, Antonio I.; Klein, Norbert; Liew, Yun Fook; Breese, Mark B. H.; Hong, Minghui; Maier, Stefan A.
<x xml:space="preserve">Abstract</x> An Otto prism coupling setup with a spoof plasmon surface underneath is the centerpiece of work by S. A. Maier and co‐workers, in which terahertz liquid sensing with figures‐of‐merit as high as 49 are demonstrated. On page 543, water molecules are shown to go onto the spoof plasmon surface, which consists of linear arrays of subwavelength grooves, tightly confining the spoof plasmons. The plasmons are sensitive to the refractive index of the dielectric filling the grooves, and phase jumps at spoof plasmon resonances provide the readout response. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>